REVIEW OF RELIABILITY AND USABILITY FACTORS IN WEB-BASED APPLICATIONS DOKUMEN PERJALANAN REPUBLIK INDONESIA VERSION 2.0 IMPLEMENTATION AT THE KANTOR IMIGRASI KELAS II NON TPI WONOSOBO - Muhammad Taufiq Akbar Fitriyanto (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
Technology develops along with the increasingly strong urge of human desire for a better and better life, a utopian ideal that seems never ending. Technology tends to be chosen as the answer to almost all problems that occur during human life in this modern era. As a modern organization, the Directorate General of Immigration also makes technology development the answer to existing problems. The restructuring of SIMKIM from version 1.0 to SIMKIM version 2.0 is clear evidence of the seriousness of the Directorate General of Immigration in realizing better implementation of immigration functions, one of which is in terms of passport issuance services. DPRI version 2.0 application is an application that is currently the key to the quality of passport issuance services throughout Indonesia. Therefore, the application should have sufficient quality in order to guarantee the achievement of the expected utopian ideal conditions. This study uses a descriptive research method with a combination approach or mix method in order to provide a more comprehensive overview of the quality of the DPRI version 2.0 application, in terms of reliability and usability factors.